(untitled) (African Journal of Public Administration & Management, 2026)
Zambia’s commitment to the 2030 Agenda for Sustainable Development underscores its pursuit of inclusive governance, transparency, and accountability. The amended Zambian Constitution (1991; 2016) enshrines sustainable development as a core national value, with land administration emerging as a critical driver of rural development. In this context, traditional leadership and community-based governance structures play a pivotal role. Zambia’s dual land tenure system, comprising state and customary land, presents unique governance challenges and opportunities. Under the Lands Act No. 29 of 1995, land ownership is vested in the President on behalf of the people. State land, administered by government entities, is titled and leasehold, while customary land governed by traditional authorities such as Chiefs and village Headpersons remains untitled and regulated by local norms. Despite efforts to formalize land rights through the National Lands Policy (2021), traditional leaders retain custodianship of customary land, shaping rural development trajectories. This study examined how partnerships between state and customary systems can promote sustainable development, especially under the auspices of a decentralized governance system. Using a qualitative, exploratory approach, the research was guided by the Institutional Analysis and Development (IAD) Framework and Good Governance theory, chosen for their complementary nature in analyzing institutional interactions and evaluating participatory, equitable governance practices in land tenure systems. The study aims to highlight institutional synergies and conflicts, proposing a governance model that aligns local legitimacy with national policy goals. The study revealed that Zambia’s dual land tenure system creates ambiguity, weak institutional collaboration, and uneven land preferences. These challenges undermine sustainable rural development, making it necessary to establish a transparent, inclusive, and coordinated land governance model that harmonizes the roles of traditional authorities, local authorities, and the state.